Achieving an Ideal Position of the Tube in Anterior Chamber: A New Approach. Issue 1 (2017) - Kumar, Harsh; Gupta, Avnindra; Gupta, Viney
Aim: To describe a novel technique of tube placement in the anterior chamber. Methods: In this technique, the extra cut piece of the tube is used to provide a hinge/fulcrum such that the main tube entering the anterior chamber would be angulated posteriorly away from the cornea. Results: The tube entering the anterior chamber is angulated posteriorly. Conclusions: Using a fulcrum beneath the tube would assist in posterior positioning of the tube and prevent long-term tube endothelial touch.